2012
DOI: 10.1016/j.gca.2011.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Iodine dynamics in soils

Abstract: We investigated changes in iodine ( 129 I) solubility and speciation in nine soils with contrasting properties (pH, Fe/Mn oxides, organic carbon and iodine contents), incubated for nine months at 10 and 20°C. The rate of 129 I sorption was greater in soils with large organic carbon contents (%SOC), low pH and at higher temperatures. Loss of iodide (I À ) from solution was extremely rapid, apparently reaching completion over minutes-hours; iodate (IO À 3 ) loss from solution was slower, typically occurring over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
119
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 75 publications
11
119
2
3
Order By: Relevance
“…Recent research confirmed older findings that iodide cannot be considered as a nonreactive tracer because it is immobilized in soils in the form of organically bound iodine (Behrens, 1982) through the laccasecatalyzed oxidation (Seki et al, 2013). It was found that iodide was fully transformed into organic forms after 1 day of incubation in highly organic soils and was fully transformed in the studied soils after 60 days (Shetaya, 2011). Therefore, the NaI solution was added in our experiment as a carrier to prevent 131 I from incorporation into organic compound and field microorganisms.…”
Section: Radioactive Tracer Experimentssupporting
confidence: 78%
“…Recent research confirmed older findings that iodide cannot be considered as a nonreactive tracer because it is immobilized in soils in the form of organically bound iodine (Behrens, 1982) through the laccasecatalyzed oxidation (Seki et al, 2013). It was found that iodide was fully transformed into organic forms after 1 day of incubation in highly organic soils and was fully transformed in the studied soils after 60 days (Shetaya, 2011). Therefore, the NaI solution was added in our experiment as a carrier to prevent 131 I from incorporation into organic compound and field microorganisms.…”
Section: Radioactive Tracer Experimentssupporting
confidence: 78%
“…The spherical diffusion model is based on the assumption that sorption is controlled by diffusion into uniform spherical particles of radius (r) controlled by a diffusion coefficient (D) [16][17][18]. It has been successfully applied to describe time-dependent sorption processes in materials, including soil [19,20], minerals [21] activated carbon [22] and waste materials e.g.…”
Section: Spherical Diffusion Modelmentioning
confidence: 99%
“…Iodide is immobilized in soils in the form of organically bound iodine through the laccasecatalyzed oxidation (Seki et al 2013). It was found that iodide was fully transformed into organic forms after 1 day of incubation in highly organic soils and was fully transformed in the studied soils after 60 days (Shetaya 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, field irrigation experiment combined with radioactive tracer technique may provide valuable data (e.g., spatial and temporal variations of applied tracer), which serve for model calibration and validation (Alaoui et al 1997). Shetaya (2011) presented the distribution coefficient K d of iodide for woodland and arable soil equal to 3.8 and 5.3 L kg −1 , respectively, and Mikolajków (2003) found that K d of nitrate for brown, podsolic, and boggy soil were 5.22, 4.29, and 6.25 L kg −1 , respectively. As iodide and nitrate retardation in soils are similar, we used radioactive iodide as a tracer for nitrate movement in clay loam soil.…”
Section: Introductionmentioning
confidence: 99%